Oncolytic adenovirus ORCA‐010 increases the type 1 T cell stimulatory capacity of melanoma‐conditioned dendritic cells - López González, M. (Clin Exp Immunol, 2020)
Immune checkpoint blockade has resulted in durable responses in patients with metastatic melanoma, but only in a fraction of treated patients. For immune checkpoint inhibitors (ICI) to be effective, sufficient infiltration with tumor‐reactive T cells is essential. Oncolytic viruses (OV) selectively replicate in and lyse tumor cells and so induce an immunogenic form of cell death, providing at once a source of tumor‐associated (neo)antigens and of danger signals that together induce effective T cell immunity and tumor infiltration. Melanoma‐associated suppression of dendritic cell (DC) differentiation effectively hampers OV‐ or immune checkpoint inhibitor (ICI)‐induced anti‐tumor immunity, due to a consequent inability to prime and attract anti‐tumor effector T cells. Here, we set out to study the effect of ORCA‐010, a clinical stage oncolytic adenovirus, on DC differentiation and functionality in the context of human melanoma. In melanoma and monocyte co‐cultures, employing a panel of five melanoma cell lines with varying origins and oncogenic mutation status, we observed clear suppression of DC development with apparent skewing of monocyte differentiation to a more M2‐macrophage‐like state. We established the ability of ORCA‐010 to productively infect and lyse the melanoma cells. Moreover, although ORCA‐010 was unable to restore DC differentiation, it induced activation and an increased co‐stimulatory capacity of monocyte‐derived antigen‐presenting cells. Their subsequent ability to prime effector T cells with a type I cytokine profile was significantly increased in an allogeneic mixed leukocyte reaction. Our findings suggest that ORCA‐010 is a valuable immunotherapeutic agent for melanoma.